De-escalating treatment indications for patients who achieve metabolic goals - García-Ulloa, Ana Cristina; Jaime-Casas, Salvador; Rosado-Lozoya, Johanna S.; Serrano-Pérez, Nancy H.; Hernández-Juárez, Diana; Cárdenas-Fragoso, José Luis; Briones-García, Luis Eduardo; Jiménez-Soto, Rodolfo; García-Padilla, Carlos; García-Lara, Juan; Aguilar-Salinas, Carlos A.; Hernández-Jiménez, Sergio (Elsevier, 2024)
Introduction: Robust evidence exists regarding initiation, intensification or modification of treatments. Recommendations to de-escalate therapy are lacking, specifically in diabetes. A successful treatment de-intensification reduces overtreatment, polypharmacy, and risk of adverse effects. Objective: To encompass current recommendations for deprescribing common drugs and create a consensus among health professionals. Methods: We reviewed four databases for deprescribing approaches published between 2010 and 2022. Articles were divided into different groups of drugs (for uric-acid, hypoglycemic, lipid-lowering, and psychotropic drugs).©Elsevier
Keywords: De-escalating; De-intensification; Diabetes; Dyslipidemia; Metabolic control; Uric acid